A comparison of phase imaging and quantitative susceptibility mapping in the imaging of multiple sclerosis lesions at ultrahigh field - Cronin, Matthew John; Wharton, Samuel; Al-Radaideh, Ali; Constantinescu, Chris; Evangelou, Nikos; Bowtell, Richard W.; Gowland, Penny A. (Springer, 2016)
Objective